ANALISIS SEMIOTIKA ROLAND BARTHES PADA KESENIAN RODAT BOYOLALI - Reny Atika Asya'roni (Yayasan Nusantara Hasana Berdikari, 2023)
Each region must have its own characteristics, culture and art. An example is Rodat Art from Boyolali. Until now, the Rodat art is still being preserved by the Boyolali people while still performing in this modern era. Rodat's art adheres to the teachings of Islam and collaborates with Javanese cultural lyrics. The characteristic and interesting thing about Rodat Art is that the community preaches but through performances that create a lively atmosphere. This research was conducted using qualitative methods and using Roland Barthes's semiotic analysis. The purpose of this research is to analyze denotative meaning, connotative meaning, myths and ideology of Rodat art. From this research, the results or conclusions can be drawn of a denotative meaning of Rodat art which contains a series of activities in preaching using cultural acculturation, where what is seen (visually) is always marked through gestures or gestures, clothing or clothes and colors. The verbal meaning is marked with prayer and the audio is marked with tambourines. There are connotative meanings that are closely related to Islamic teachings, such as: poems, creeds, Sholawat poems and Javanese poetry of Sunan Kalijaga. Many myths and ideologies, called hierophanies, are collective religious expressions, religiosity and religion have a role as a cultural system.